Agroindustrial best practices that contribute to technical efficiency in Brazilian sugar and ethanol production mills. (15th June 2019) - Lemos, Stella Vannucci; Salgado, Alexandre Pereira; Duarte, Alexandre; de Souza, Marco Antonio Alves; de Almeida Antunes, Fernanda
Abstract: The agricultural and industrial indicators that contribute to the efficiency of sugarcane mills were investigated in this study. A two-stage Data Envelopment Analysiswith output approach was applied to 271 mills for the data from the 2006/2007 season to the 2015/2016 season. The first stage consisted of the elaboration of two efficiency models using the total milling yield of the crop (t) and the amount of total recoverable sugars (t) as the input variables and the productions of sugar (t) and ethanol (m 3 ) as the output. The second stage identified the production process variables significantly influencing the efficiency through multiple linear regression. In addition, with the help of sugarcane experts, ten variables related to the efficiencies of the agricultural and industrial processes of sugar and ethanol production, which contribute to the overall productivity of the sugar-energy units, and 40 best practices were developed to observe, improve, and control these indicators in order to increase the global efficiency of the agroindustrial production units. Highlights: Best practices improve competitiveness of a production unit. Improvements in agricultural sector affects directly the global efficiency. Ten variables represent the most important control points in agroindustry plants. Field, structural and operational factors set the agroindustrial best practices. Adopt the best agroindustrial practices increase technical efficiency.